2021
DOI: 10.1177/2382120521992323
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Detailed OSCE Score Reporting on Learning and Anxiety in Medical School

Abstract: Introduction There is growing literature on increasing feedback from Objective Structured Clinical Examinations (OSCEs) and one approach is a score report. The purpose of this study was to implement and evaluate a score report for a second and fourth-year medical school OSCE. Methods We developed an electronic OSCE score report that displayed comments and performance by domain within and across stations (checklist items and rating scales were tagged to each domain). Our initial pilot released the score report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…One study showed that the OSCE is one of the most anxiety-producing assessments for learners [38]. Improving examiner training, reducing the time between the exam and getting feedback on the results, and allowing students to fully understand the feedback may be one strategy for reducing immediate anxiety [39].…”
Section: Analysis Of the Questionnaire Results About Students' Views ...mentioning
confidence: 99%
“…One study showed that the OSCE is one of the most anxiety-producing assessments for learners [38]. Improving examiner training, reducing the time between the exam and getting feedback on the results, and allowing students to fully understand the feedback may be one strategy for reducing immediate anxiety [39].…”
Section: Analysis Of the Questionnaire Results About Students' Views ...mentioning
confidence: 99%
“…The teaching staff decided that once the OSCE had been completed, it should be the actress who had to evaluate the student. The actress was provided with and given training for the evaluative checklist of this periodontology station, which consisted of 15 questions with a yes or no answer options, which had been modified from prior studies [20][21][22]. The items that had to be completed by the actress dealt with the NG itself, as well as the management of her nervous attitude on the part of the student.…”
Section: Discussionmentioning
confidence: 99%